Efficacy of antithymocyte globulin for allogeneic hematopoietic cell transplantation: a systematic review and meta-analysis. Issue 8 (3rd August 2017) - Arai, Yasuyuki; Jo, Tomoyasu; Matsui, Hiroyuki; Kondo, Tadakazu; Takaori-Kondo, Akifumi
Abstract: The efficacy of rabbit antithymocyte globulin (ATG) for the prevention of graft-versus-host disease (GVHD) has been evaluated in several randomized control trials, but the results show some discrepancies. Therefore, we performed a systematic review and meta-analysis covering the latest RCTs including six trials (total 845 patients). The incidence of acute and chronic GVHD was significantly lower in the ATG arms (risk ratio, 0.75 and 0.54, respectively). No significant differences were found regarding overall survival, the incidence of relapse, and non-relapse mortality; however, the incidence of cytomegalovirus and Epstein-Barr virus reactivation increased (risk ratio, 1.25 and 1.33), and neutrophil engraftment was significantly delayed (median, 2.66 days). In conclusion, rabbit ATG should be beneficial as a GVHD prophylaxis in addition to conventional regimens, with close monitoring of virus reactivation and enough attention to delayed engraftment. Studies comparing the timing and dosage of ATG are essential to determine the suitable prophylactic regimens.